Currency Mismatches and Public Debt Management: What is Effective Strategy for Developing Country? - MOUANDAT, Scott Regifere (Journal of Empirical Studies, 2022)
Developing countries are often confronted with debt problems because of the risks of over-indebtedness and especially the heavy default history. In such a context, debt management must be rigorous and guarantee a stable debt. However, such management is difficult in an environment marked by liabilities denominated in foreign currencies and assets denominated in domestic currencies, i.e., an environment of currency mismatches. The objective of this paper is then to determine, from a partial equilibrium model, an effective strategy for managing public debt in the presence of currency mismatches. We conclude that it is preferable to arbitrate between a debt denominated in foreign currency and a debt denominated in domestic currency. We also find that this arbitation depends on the financing conditions, i.e. the domestic interest rate and the risk premium on foreign debt. More precisely, when the government's objective is to minimize the interest burden, it is preferable to issue more local currency debt and less foreign currency debt, as long as the domestic interest rate is lower than the risk premium on foreign debt.